Segregación estacional por sexo y edad de venado cola blanca en poblaciones de vida libre y encierro en Durango, México - Vega-Hernández, Dania Melissa; Gallina-Tessaro, Sonia Antonieta; Correa-Ramírez, Miguel Mauricio; Chairez-Hernández, Isaias; Soto-Cárdenas, Miguel Angel (Instituto de Ecología, A.C., 2019)
White-tailed deer (Odocoileus virginianus) is a species with great economic and ecological relevance in Mexico, since it is the main game species in the country. Therefore, it is necessary to obtain reliable demographic data to improve its management. However, animal segregation movements could bias the population density estimations and demographic trends. This work aimed to analyse seasonal segregation by sex and age in free-living and fenced populations of white-tailed deer based on faecal groups. Fresh faecal groups of white-tailed deer were collected in two Wildlife Conservation Management Units (UMA in Spanish) located in Durango, Mexico: Salvador Allende and Molinillos. Faecal groups were collected every two weeks during 13 months for each UMA (from March 1st, 2015 to March 31st, 2016 for Salvador Allende, and from October 1st, 2015 to October 31st, 2016). The length and width of 10 faecal pellets were measured and the mean volume was calculated for each faecal group. Then, faecal groups were assigned to an age and sex category by a fuzzy set clustering technique. DNA was isolated from faecal pellets and a fragment of the SRY gene was amplified to determine the sex of the animals that deposited the faecal groups, in order to compare with the information obtained with the morphometric data of the pellets. The spatial-temporal data taken from faecal groups and the identification of age and sex were used for spatial sexual segregation coefficient (CSSE) calculation. Data about temperature, precipitation, photoperiod and vegetal cover were obtained for every season. A total of 351 fresh faecal groups were collected for both UMAs, in general, more faeces belonging to females. A lower number of faecal groups was collected in Salvador Allende (112). In both UMAs the lowest number of faecal groups was found in summer. The largest number of faecal groups was found in winter in Salvador Allende and in autumn in Molinillos. Statistic differences between segregation index between seasons was found. The sexual segregation index was higher in summer in both UMA (0.910 for Salvador Allende and 0.943 for Molinillos) when fawning occurred. By contrast, the lowest value was observed in winter (0.339) for Salvador Allende and in autumn (0.130) for Molinillos, when the breeding season occurred. Generally, reproductive behaviour determined age and sexual segregation. The highest proportion of faecal groups of juveniles was observed in spring and autumn in Salvador Allende and in summer in Molinillos. There was no correlation between sexual segregation index and environmental variables. It is necessary to consider variations in the segregation patterns in each season, since they can affect the population estimations based on the faecal counting technique. It is recommended to make the population estimates in seasons which spatial sexual segregation coefficient shows the highest and the lowest values.